The gig economy : a critical introduction - Woodcock, Jamie; Graham, Mark, 1980- (Cambridge, UK ; Medford, MA : Polity Press, 2020)
"All of a sudden, everybody's talking about the gig economy. Drawing upon years of research, stories from gig workers, and a review of the key trends and debates, Jamie Woodcock and Mark Graham shed light on how the gig economy came to be, how it works and what it's like to work in it".
Where did the gig economy come from? -- How does the gig economy work? -- What is it like to work in the gig economy? -- How are workers reshaping the gig economy? -- Conclusion: What's next for the gig economy?
Includes bibliographical references and index.
Keywords: Precarious employment; Temporary employment; Independent contractors